KARAKTERISTIK IBU DALAM MENUNJANG PERTUMBUHAN DAN PERKEMBANGAN ANAK BALITA - Farida, Siti Nur; Hidayah, Ardiyanti; Anggraini, Rista Dian (PRIMA WIYATA HEALTH, 2025)
Background: Children's lives are a crucial stage of development that has to be supported. This stage is characterized by extremely quick physical, psychomotor, mental, and social development and growth. 34.3% of parents do not take their children's growth and development into account. As a result, many children's growth and development have not been monitored. 33.5% of kids are thought to have developmental issues. Objectives: To monitor the progress and development of toddlers at the Kesamben Public Health Center in Jombang Regency, the study set out to identify the characteristics of toddler mothers. Methods: Cross-sectional approach in a descriptive study design. The study's samples, which were chosen by chance, consisted of up to 53 mothers of toddlers. Data analysis employs univariate analysis. Results: Twenty-seven mothers (50.9%) had a high family income, thirty mothers (56.6%) were between the ages of twenty and thirty-six, thirty mothers (54.8%) had completed high school, thirty mothers (69.8%) had two or more children, and forty-four mothers (83%), did not work, according to the findings.   Conclusion: The study findings indicate that most mothers of toddlers at Posyandu Dahlia, Kesamben Public Health Center, Jombang Regency are in the productive age range, have completed high school education, have high family income, have two or more children, and are not employed. These characteristics influence mothers' involvement in monitoring their children's growth and development. Mothers with higher education and stable income tend to have better awareness of child growth monitoring. Additionally, unemployed mothers have more time to participate in Posyandu activities compared to working mothers. This study highlights the need for increased parental awareness and education programs to enhance child growth monitoring, particularly among mothers with lower education and income levels. Strengthening health education and parental support is essential to improve children's overall health and development outcomes.